2013
DOI: 10.18514/mmn.2013.906
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries for thought

Abstract: This paper covers several topics that involve symmetries of differential equations: from the connection between Lie symmetries and Jacobi last multiplier with a detour to the inverse problem of calculus of variations, to the importance of maximal group of Noether symmetries on the road from classical to quantum mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(23 reference statements)
0
6
0
1
Order By: Relevance
“…В работе [15] такая же схема квантования использовалась, чтобы квантовать уравнение Риккати второго порядка, а в работе [16] было выполнено квантование динамики заряженных частиц в однородном магнитном поле и неизохронной системы "золотой рыбки" Калоджеро. В статье [17] этот метод поволил получить уравнение Шредингера для уравнения, связанного с "золотой рыбкой" Калоджеро, в работе [18] он же дал уравнение Шредингера для двух нелинейных уравнений, в какой-то степени связанных с задачей Римана [19]. В работе [20] было показано, что условие сохранения нётеровских симметрий непосредственно приводит к уравнению Шредингера в импульсном пространстве нелинейного осциллятора типа осциллятора Льенара из работы [21], а в работе [22] этот же результат был получен для семейства квадратичного уравнения типа Льенара [23].…”
Section: квантование изохронной модели "золотой рыбки"unclassified
“…В работе [15] такая же схема квантования использовалась, чтобы квантовать уравнение Риккати второго порядка, а в работе [16] было выполнено квантование динамики заряженных частиц в однородном магнитном поле и неизохронной системы "золотой рыбки" Калоджеро. В статье [17] этот метод поволил получить уравнение Шредингера для уравнения, связанного с "золотой рыбкой" Калоджеро, в работе [18] он же дал уравнение Шредингера для двух нелинейных уравнений, в какой-то степени связанных с задачей Римана [19]. В работе [20] было показано, что условие сохранения нётеровских симметрий непосредственно приводит к уравнению Шредингера в импульсном пространстве нелинейного осциллятора типа осциллятора Льенара из работы [21], а в работе [22] этот же результат был получен для семейства квадратичного уравнения типа Льенара [23].…”
Section: квантование изохронной модели "золотой рыбки"unclassified
“…We apply this method to the Schrödinger equation (26). Let us rewrite the Lie point symmetries (28) of equation (26) in complex form, i.e.…”
Section: Equation (21)mentioning
confidence: 99%
“…A new algorithm for quantization that requires the preservation of Noether symmetries in the passage from classical to quantum mechanics 16 has been recently introduced and applied to both one-dimensional and two-dimensional Lagrangian equations [11,[23][24][25][26][27].…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] the same quantization scheme was applied in order to quantize the second-order Riccati equation, while in [9] the quantization of the dynamics of a charged particle in a uniform magnetic field in the plane and Calogero's goldfish system were achieved. In [10] the same method yielded the Schrödinger equation of an equation related to a Calogero's goldfish, and in [11] that of two nonlinear equations somewhat related to the Riemann problem [12]. In [13], and [14] it was shown that the preservation of the Noether symmetries straightforwardly yields the Schrödinger equation of a Liénard I nonlinear oscillator in the momentum space [15], and that of a family of Liénard II nonlinear oscillators [16], respectively.…”
Section: Introductionmentioning
confidence: 95%